The relationship amid land finance and economic growth with the mediating role of housing prices in China - Sun, Qian; Feng, Yan; Tang, Yong; Kuang, Wen; Javeed, Sohail Ahmad (Frontiers in Psychology, 2022)
Taking cities at prefecture-level and above nationwide as the research object, we theoretically analyze the effects of land finance on housing prices and economic growth as well as the effects of housing prices on economic growth, consider the mediating role of housing prices, and construct a random-effects model of land finance affecting economic growth. The 278 resource-based cities with relatively well-developed land and real estate markets are selected to test the mediating effect of housing prices on land finance affecting economic growth in resource-based cities by type based on panel data from 2011–2019. The results show that (1) land finance significantly and positively affects economic growth and housing prices in cities at the prefecture-level and above nationwide, but there is some variability in the degree of influence. The central region has the smallest impact on economic growth but the largest impact on housing prices; the eastern region has the deepest impact on economic growth; and the western region has the smallest impact on housing prices. (2) In the national sample cities and cities in the northeast region, housing prices have a significant partial mediating effect on economic growth affected by land finance, with 22.03% and 2.84%, respectively. The mediating effect of urban housing prices on land finance affects economic growth in the eastern, central, and western regions is not significant. The mediating effect is defined as 0.